Wise-PRoPHET: A Watchdog supervised PRoPHET for reliable dissemination of post disaster situational information over smartphone based DTN. (1st May 2018) - Basu, Souvik; Biswas, Ayanesh; Roy, Siuli; DasBit, Sipra
Abstract: Delay tolerant network (DTN) has been successfully proposed for setting up emergency post disaster communication networks when normal communication infrastructure is typically incapacitated. These networks work on the basis of cooperation from participating nodes, which is cost-intensive in terms of battery life, computation, etc. Therefore, nodes can refuse to cooperate to save resources, giving rise to selfish nodes that hinder the transmission of sensitive post disaster situational messages. Another issue is the presence of malicious nodes that collude to either spoil the reputation of honest nodes or boost the reputation of selfish nodes. The existing DTN routing protocols, like PRoPHET, do not address these issues. In this paper, a trust based Watchdog technique is seamlessly integrated with PRoPHET so that situational messages are successfully delivered even in the presence of selfish and malicious nodes. The Watchdog monitors its neighbouring nodes to generate a local perception about their forwarding behaviour. This information is then disseminated in the network to build a global perception of forwarding behaviour for detection of selfish nodes. The local perception is further used to identify malicious nodes in the network. The proposed technique rationalizes self-trusting, a property of trust based data forwarding in opportunistic networks which reduces and delays message transfers, to further improve delivery ratio and delay. Results of extensive simulation, using ONE simulator, substantiate the efficiency of the proposed Watchdog enabled PRoPHET over state-of-the-art competing schemes, in terms of detection ratios, attraction ratio, etc. while not compromising standard network performance. Finally, it is claimed that the proposed technique, tolerates a reasonable percentage of selfish and malicious nodes to achieve a desirable level of network performance, in a post disaster communication scenario. Highlights: Integrates a trust based Watchdog with PRoPHET to avoid selfish and malicious nodes. Watchdog monitors neighbours to generate local trust values. Local trust values are combined to build global trust values for detecting selfish nodes. Local trust values are further used to identify malicious nodes in the network. Trust values provided by malicious nodes are ignored while computing forwarder trust.